Evaluation of the Psychometric Properties of the Greek version of Active Life with Asthma - ALMA (Gr-ALMA) tool - Livadiotis, Chris (Department of Nursing, Faculty of Health Sciences, Cyprus University of Technology, 2017)
While the burden of asthma is high, there are problems with the delivery of care, such as under-treatment with corticosteroids. Furthermore, there is often poor asthma knowledge and self-management skills among patients with asthma. Regular asthma reviews are recommended by international guidelines to improve asthma morbidity and the quality of life of asthma patients. To facilitate these reviews in primary care practice, there is a need for structured asthma review tools.
Keywords: Asthma; Self-management; Asthma control; Metric properties; Quality of Life